Evaluasi dan Rekomendasi Perbaikan Proses Pemenuhan Permintaan Layanan Teknologi Informasi: Studi Kasus PT Bank XYZ - Permatasari, Yuniar; Aji, Rizal Fathoni (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
As digital payments in Indonesia increase, they drive the financial industry, especially banking, to continue their digital transformation. BANK XYZ is one of the banks that is also undergoing digital transformation. To improve banking services that are always available and meet market demand, it is necessary to fulfill the demand for information technology (IT) services. However, there is a problem in this process, namely that many requests are not followed up and closed even though they have been worked on, causing delays in fulfilling user requests. Therefore, this research aims to evaluate the process of fulfilling IT service requests and provide improvement recommendations for the future. The evaluation process in this study uses the COBIT 2019 framework to measure the capability of relevant process areas, and ITIL V4 provides good practices for process improvement recommendations. After data collection and capability measurement on eleven processes, the results showed that three processes were at level two, namely APO09, BAI08, and BAI10. There are five processes at level three, namely BAI07, BAI08, DSS02, DSS03, and DSS04. For the achievement of level four, there are two processes, namely APO14 and BAI06, and one process that has reached the level, namely DSS01. Then, in the gap analysis process, there are three processes that have met the management's targets, namely APO14, BAI06, and DSS01, and eight processes that have not yet met the targets. Recommendations are given for the eight processes that have not yet met the management's expected targets.